Management of dental caries lesions in patients with disabilities: Update of a systematic review - Molina, Gustavo; Zar, Mariana; Dougall, Alison; McGrath, Colman (Frontiers in Oral Health, 2022)
The aim of this systematic review was to update an existing review on the management of dental caries lesions in patients with disabilities so as to provide an up-to-date summary of the evidence. Randomized clinical trials and cohort studies related to preventive and restorative programmes for dental caries among people requiring special care, published in English, Spanish, Portuguese, French and German languages from February 1st 2011 to April 1st 2022, were retrieved from three databases (“updated review”). From the 1,105 titles identified using the search topic “Caries AND Disability”, 17 papers informed in the analyses: 6 referring to caries preventive strategies and 11 related to restorative care strategies. Most of these studies targeted children and adults with intellectual/physical disability, although preventive and therapeutic strategies were also reported for frail older adults and onchohematological patients. Fluorides in tablets, gels or varnishes forms and the use of xylitol as a sugar substitute were reported as effective approach to prevent the onset of caries in high-risk groups. Minimally intervention treatment options such as the Hall technique, the ART approach and the use of SDF for arresting caries, were deemed suitable and effective strategies for treating existing lesions in-office. In conclusion, in the past decade (2011–2022) an increased number of articles reported strategies to prevent and manage caries among people requiring special care. Although an array of preventive and therapeutic strategies for dental caries exists, more and better-quality clinical evidence is needed to offer guidance to inform policy and practice for special care dentistry.